(untitled) (American Journal of Islam and Society, 2006)
Books Reviewed: Jack Goody, Islam in Europe. Cambridge: Polity Press, 2004; Richard W. Bulliet, The Case for Islamo-Christian Civilization. New York: Columbia University Press, 2004; James A. Bill and John Alden Williams, Roman Catholics and Shi’i Muslims: Prayer, Passion, and Politics. Chapel Hill and London: University of North Carolina Press, 2002. There can be no doubt that the twenty-first century has begun – and continues – under the ominous cloud of enmity between Muslim groups or nations and western ones, from the attacks on American soil on 11 September 2001 to those in Madrid and London, to the invasions of Afghanistan and Iraq, and now in the growing tension with Iran. Unsurprisingly, this has spurred a mushrooming of publications on the troubled relations between “Islam and the West,” with almost every book pointing out the bold Christian rhetoric emanating from a militarily aggressive White House. Kenneth Cragg, the veteran Christian expositor of the Qur’an, more prolific than ever in his nineties (seven titles since 2002), astutely named one of his latest books The Qur’an and the West (Georgetown University Press: 2006). Not only is “Islam” misleading in terms of the wide diversity of cultures, sects, and spiritualities inspired by the Qur’an and the Hadith literature, but for Cragg, Muslims in today’s globalized world, whether living as “exiles” in the West or within Muslim-majority states, will have to choose between the vulnerable faith proclaimed in the early years in Makkah and the religion cum political rule exemplified by the Prophet in Madinah. As usual, Cragg also challenges the Christian side, which, in its American incarnation, largely rationalizes the use of power to extend its hegemony from Israel-Palestine to Central Asia in the name of democracy. Though all three books under review here share Cragg’s motivation to reduce tension and foster greater understanding between Muslims and Christians, only the third (on Shi`ites and Catholics) represents the kind of theological dialogue that Cragg and others have nourished over the years ...